2019
DOI: 10.1071/mf18096
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive strategy of the Pacific cownose ray Rhinoptera steindachneri in the southern Gulf of California

Abstract: Rhinoptera steindachneri is one of the most common batoid species in the artisanal gill net fishery of the Gulf of California. In this study we investigated its reproductive biology based on 317 specimens caught in Bahía de la Paz, Mexico. Females measured up to 94.2-cm disc width (DW) and males reached 82.5cm DW; there were no significant differences in size or weight between sexes. The median size at maturity was estimated at 68.5cm DW for males and 71.8cm DW for females, and the median size at pregnancy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
0
16
0
6
Order By: Relevance
“…Myliobatiformes males, in general, have both testes functional, with little difference in size or mass, as observed for Rhinoptera steindachneri (Burgos-Vázquez et al, 2018), M. ridens and M. goodei (Araújo et al, 2016), Rhinoptera bonasus (Poulakis, 2013) and H. guttatus (Melo, 2016).…”
Section: Histology Of the Oviducal Glandmentioning
confidence: 63%
See 1 more Smart Citation
“…Myliobatiformes males, in general, have both testes functional, with little difference in size or mass, as observed for Rhinoptera steindachneri (Burgos-Vázquez et al, 2018), M. ridens and M. goodei (Araújo et al, 2016), Rhinoptera bonasus (Poulakis, 2013) and H. guttatus (Melo, 2016).…”
Section: Histology Of the Oviducal Glandmentioning
confidence: 63%
“…The males in this study showed no significant difference between the paired structures (testes and clasper glands). Both sides of the reproductive tract of A. narinari males were functional, with the greatest observed value for L C being 184 mm, for L CG 69 mm and for M TE 155 g. Myliobatiformes males, in general, have both testes functional, with little difference in size or mass, as observed for Rhinoptera steindachneri (Burgos‐Vázquez et al ., 2018), M. ridens and M. goodei (Araújo et al ., 2016), Rhinoptera bonasus (Poulakis, 2013) and H. guttatus (Melo, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, this free‐living report should be considered doubtful. Recent biological information available for this species off the northwestern coast of Mexico confirms a birth size range between 381 to 420 mm DW (Burgos‐Vázquez et al., 2019; Ehemann et al., 2019) compared with the ≈200 mm DW abnormal specimen, meaning that the latter corresponded to a fully developed embryo. Although capture‐induced parturition has not yet been confirmed for this species (Adams et al., 2018), this scenario is also plausible to be considered for the abnormal Mexican cownose ray.…”
Section: Discussionmentioning
confidence: 88%
“…The OG has the same basic organization in most studied elasmobranchs, but the reproductive relevance of each glandular region varies (Hamlett et al ., 1998, 2005). Only the Narcinidae (electric rays, Torpediniformes) lack the OG (Prasad, 1945), and some species of Myliobatiformes have a vestigial OG (Burgos‐Vázquez et al ., 2018; Colonello et al ., 2013). Conversely, oviparous species have the largest OGs among chondrichthyans, since they produce not only the jellies that envelop the egg, but also an external capsule and all its ornamentations (Hamlett et al ., 2005; Serra‐Pereira et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%